خطة لتصميم وحدات دراسية لتعليم اللغة العربية لغير الناطقين بها في ضوء المداخل الاتصالي الثقافي : المعهد العالي للغات بجامعة حلب نموذجا - جاموس، راوية محمد عادل (Kulliyyah Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2014)
This study aims at identifying the reality pertaining to teaching the Arabic language to non-Arabic speakers at the Higher Institute of Languages at Aleppo University in order to know their needs and subsequently design study modules that suit them in the context of the communicative-cultural approach. It also aims at identifying the necessary principles in designing those modules in order to benefit from them in presenting practical prototype modules for beginner, intermediate and advanced levels. The importance of this study comes from several perspectives, the most important of which is that it presents a study to the Higher Institute of Languages explaining the needs of the learners therein, which facilitates the preparation of appropriate learning materials for them. It also has significance in that it merged between both the communicative approach and the cultural one in preparing study modules that blend between the principles of these two approaches. To achieve its objectives this study adhered to the qualitative approach through the researcher's own personal observations regarding the reality of teaching the Arabic language to non- Arabic speakers at the Higher Institute of Languages at Aleppo University, while this study also carried out interviews with teachers at the Institute in order to identify the reality of teaching the Arabic language and the needs of the learners. This study also applied the quantitative approach by having a questionnaire prepared through which the needs and motives of learners were identified. It was concluded from this study that the majority of learners at the Higher Institute of Languages focus on the communicative and cultural aspects in studying the Arabic language, which constitutes a strong incentive to study in Syria. This study also designed three prototypes for study modules for each level, taking into consideration the needs of the learners based on the results of personal observations, interviews and questionnaires, wherein the principles of the communicative-cultural approach was implemented, as well as various principles mentioned throughout this study in the design of study modules.